Raising entire male pigs: comparison of growth performance and meat quality of the Bísara breed and a terminal cross - a pilot study - Pereira-Pinto, Ricardo; Araújo, José Pedro; Cerqueira, Joaquim; Mata, Fernando; Pires, Preciosa; Vaz-Velho, Manuela (Frontiers in Animal Science, 2025)
Rearing entire male pigs presents several benefits, including enhanced feed efficiency, reduced environmental impact, and improved animal welfare. However, the risk of boar taint poses a significant challenge to pork quality. The objective of this pilot study is to evaluate growth performance, meat quality and the incidence of boar taint in intact male pigs of the Bísara breed (BI) and a terminal cross (TC). Five pigs from each breed were monitored during growth and blood samples were taken to measure tainting compounds (skatole and androstenone). The meat quality was compared concerning its colour, pH, and water-holding capacity (WHC). Bísaro pigs have more intensive muscle colour, higher WHC, and higher intramuscular fat content (p<0.001). No significant differences were noted for pH (p>0.05). TC pigs demonstrated more consistent growth patterns and faster growth during later stages. Meat quality analysis revealed statistically significant differences (p < 0.05) between the two groups in parameters such as thawing loss, moisture content, meat colour, and intramuscular fat, which favoured BI pigs. Conversely, TC pigs exhibited significantly lower levels of boar taint (p<0.05). The Bísara breed, which has not undergone intensive genetic selection, faces greater challenges in addressing boar taint compared to widely used commercial breeds. The emphasis on quantitative traits in BI breeding programs may have overshadowed the importance of qualitative traits. Therefore, exploring alternative and sustainable strategies to manage boar taint in Bísaro pigs is essential.